SEPAK BOLA DAN KESETARAAN GENDER DALAM KAMPANYE IKLAN NIKE BERTAJUK “NEVER SETTLE, NEVER DONE” - Alvicky, Angga; Sinduwiatmo, Kukuh (Universitas Tribhuwana Tungga Dewi, 2023)
With the protests and discussions about gender equality in football and the momentum of Women's EURO 2022, Nike, a clothing brand in the world's biggest sport, released a commercial titled